Real-time energy monitoring in renewable EV charging stations: An ESP32-based system integrating Modbus, MQTT, and ESP-NOW protocols - Nizam, Mohamad Syukri Mohamad; Abdullah, Ezmin; Hidayat, M. Nabil; Hashim, Nik Mohd Zarifie; Hassan, M A Abu (2024)
The global shift toward electric vehicles (EVs) has created a critical need for efficient and sustainable renewable-powered EV charging infrastructure. This paper presents an innovative ESP32-based energy monitoring system integrating Modbus, MQTT, and ESP-NOW protocols to address challenges in real-time energy management and communication. The system monitors key components, including the grid, solar panels, EV chargers, and energy storage systems (ESS), using four ESP32 units as data senders. Data is collected locally via Modbus, transmitted to a central ESP32 receiver using ESP-NOW for peer-to-peer communication, and visualized on a cloud platform (Thingsboard) using MQTT. Testing conducted within a 5-30 meters range demonstrated reliable local data acquisition, consistent 5 -second updates through MQTT, and optimized communication via ESP-NOW with a payload limit of 250 bytes. Results confirm the system’s scalability, reliability, and suitability for low-cost implementation in renewable-powered EV charging networks, offering real-time monitoring and operational insights essential for efficient energy distribution.